The Comparative Study on the Application Value of Transperineal Prostate Combined Biopsy and Transrectal Prostate Systematic Biopsy in Diagnosing Prostate Cancer in Patients with Different PSA Zones - Wang, Hailuo; Wang, Hao; Gao, Wen; Xu, Peng; Wang, Jingkai; Xu, Hao; Pan, Deng; Ma, Yuyang; Zhang, Ruoran; Zhang, Peiyong; et al. (Urology Journal, 2025)
Purpose: This study aimed to compare the effects of transperineal prostate combined biopsy (TP-CB) and transrectal prostate systematic biopsy (TR-SB) on the detection rate and safety of prostate cancer in patients with prostate-specific antigen (PSA) gray zone, PSA levels of 10 20 ng/mL, and 20 40 ng/mL, and explore the comparative value of their applications. Materials and Methods: We collected 243 samples from patients with PSA ≤ 40 ng/mL who underwent prostate biopsy. All patients were divided into two groups according to different patterns of prostate biopsy. The detection rates of prostate cancer and clinically significant prostate cancer (CsPCa) in patients with PSA levels of 4 10,10 20, and 20 40 ng/mL were compared between two different biopsy methods, surgical conditions, and the incidence of complications. Results: The rate of a positive prostate cancer biopsy was significantly higher in TP-CB than in TR-SB (P < 0.05). Further subgroup analyses revealed no statistical significance in the rate of positive prostate cancer biopsy in patients with PSA levels of 4 10 and 20 40 ng/mL between the two groups (P > 0.05). However, patients with PSA levels of 10 20 ng/mL in the TP-CB group exhibited a higher detection rate (P < 0.05), with CsPCa accounting for a higher proportion. The TP-CB and TR-SB groups did not exhibit a significant difference in surgical conditions or overall complication rates (P > 0.05). However, the TR-SB group exhibited a higher risk of postoperative febrile infection than the TP-CB group (P < 0.05). Conclusion: For patients with PSA in the ’sub-gray zone’ (10 20 ng/mL), TP-CB has a better diagnostic and application value and is more suitable for clinical promotion.